A review of empirical evidence on gender differences in nonland agricultural inputs, technology, and services in developing countries - Peterman, Amber; Behrman, Julia A.; Quisumbing, Agnes R. (International Food Policy Research Institute, 2010)
This paper reviews existing microeconomic empirical literature on gender differences in use, access, and adoption of nonland agricultural inputs in developing countries. This review focuses on four key areas: (1) technological resources, (2) natural resources, (3) human resources, and (4) social and political capital. In general, there has been more empirical research on inorganic fertilizer, seed varieties, extension services, and group membership than on tools and mechanization, life-cycle effects, and political participation. Across input areas, generally men have higher input measures than women; however, this finding is often sensitive to the use of models that control for other background factors, as well as the type of gender indicator implemented in the analysis. We find few studies that meet our inclusion criteria outside Sub-Saharan Africa. Finally, future directions, opportunities, and recommendations for microeconomic gender analysis of nonland agricultural inputs are discussed.